Psychiatric disorders, depression and quality of life in patients with psychogenic non-epileptic seizures and drug resistant epilepsy living in Argentina. (November 2021) - Scévola, Laura; Wolfzun, Camila; Sarudiansky, Mercedes; Pico, María Marta Areco; Ponieman, Micaela; Stivala, Ernesto Gonzalez; Korman, Guido; Kochen, Silvia; D'Alessio, Luciana
Highlights: Psychiatric comorbidity is frequent in people with psychogenic non-epileptic seizures and drug resistant epilepsy. In this study, trauma and somatization were associated with psychogenic non-epileptic seizures. Lower quality of life was found in patients with psychogenic non-epileptic seizures. Higher history of suicide attempts was found in patients with psychogenic non-epileptic seizures. Abstract: Objectives: Psychiatric disorders are frequently found in both patients with PNES and DRE, making the differential diagnosis even more complex. The aim of this study was to analyze and compare psychiatric aspects and the quality of life in patients with psychogenic non-epileptic seizures (PNES) and drug resistant epilepsy (DRE). Methods: Patients admitted to video-electroencephalograpy (VEEG) unit with confirmed PNES and DRE were included. Demographical characteristics, psychiatric diagnosis according to SCID I and II of DSM IV, pharmacological treatment, general functioning measured with GAF (Global assessment of functionality), quality of life (QoL) using QlesQSF (Quality of Life Enjoyment and Satisfaction Questionnaire Short Form) and depression severity using BDI II (Beck depression inventory), were compared between the groups. Non-parametric tests, chi square test, and logistic regression were used for statistical analysis. Results: 148 patients consecutively admitted to VEEG were included (DRE n  = 97; PNES n  = 51). Somatization disorder (RR: 13.02, 95% CI: 1.23–137.39, p  = 0.03) and a history of trauma (RR: 8.66, 95% CI: 3.21–23.31, p  = 0.001) were associated with PNES. The QlesQ score and the GAF score were lower with a higher prevalence of suicide attempts in the PNES group ( p  < 0.01). A negative correlation was observed between the severity of depression and the quality of life (DRE r  = - 0.28, p  = 0.013; PNES r  = - 0.59, p  = 0.001). Conclusions: Higher psychiatric comorbidity with poorer QoL were found in PNES patients compared to DRE. However, depression comorbidity negatively affected the QoL in both groups. Future studies based on illness perception will be orientated to complete this analysis.